Effect of indentation depth in impression creep test: conversion relationships and correction functions. (3rd September 2021) - Li, S.; Purdy, D.; Brett, S.J.; Deng, D.; Shibli, A.; Sun, W.
ABSTRACT: The impression creep test method has been used extensively to determine the in-service creep properties of power plant components from a small volume of material. In the standardisation of the impression creep test, the determination of a maximum 'allowable' indentation depth is an important issue. This paper presents the results of finite element analyses obtained using a simplified method based on steady-state creep, for evaluating the variation of conversion factors with indentation depth. The results obtained show that the indentation depth has a significant influence on the conversion parameters and the steady-state creep deformation rate when the indentation depth is sufficiently large. On this basis, recommendation on practical application of these conversion relationships was made to the users, and empirical formulas were provided for the possible corrections of the conversion factors. The effect of plastic zone due to initial loading on the subsequent creep was found to be insignificant.